The approach of the human resources management department on stres management in hospital administaration: and a research - Geniş, Nihan (My University, 2010)
Stresi, Stres Yönetimi, Hastaneler, Hastane Yönetimi ÖZET İNSAN KAYNAKLARI DEPARTMANININ HASTANENELERDE STRES YÖNETİMİNE BAKIŞI VE BİR ARAŞTIRMA Bu tanımlayıcı çalışmanın temel amacı sağlık çalışanları arasındaki stres ve stres azaltıcı faktörleri araştırmaktır. Çalışma İstanbul’ da sağlık sektöründe hizmet veren bir özel hastane ile aynı kuruma bağlı hizmet veren iki farklı poliklinikte uygulanmıştır. Araştırmaya 314 personel katılmıştır. Veriler anket yöntemiyle elde edilmiştir. Uygulanan anketin ikinci bölümü Milli Prodüktivite Derneği tarafından geliştirilmiş anket sorularından ve literatür çalışması sonucunda elde edilen sorulardan, üçüncü bölüm ise literatür çalışması sonucunda elde edilen sorulardan oluşturulmuştur. Elde edilen sonuçlar sağlık çalışanlarının meslek grupları ve görev yaptıkları kurumlara göre farklı stres ve stres azaltıcı faktörleri olduğunu göstermektedir. Occupational Stress, Stress Management, Hospitals, Hospital Management

THE APPROACH OF THE HUMAN RESOURCES MANAGEMENT DEPARTMENT ON STRESS MANAGEMENT IN HOSPİTAL ADMİNİSTARATİON : AND A RESEARCH The main purpose of this descriptive study was to investigate the work related stressors and stress reducing factors among healthcare staff. The survey was applied to one hospital and two different clinics of it which were serving in health sector in Istanbul. 314 personnel participate in this research. The data was collected by using inventory. The second part inventory, include the test questions which were developed by National Productivity Center and the questions prepared by litterateur study . Third part of the survey was prepared by litterateur study. Attainment results indicated that healthcare staffs have different types of stressors as well as stress reducing factors in accordance with their occupation and institution.
Keywords: Hastane Yönetimi; Hastaneler; İnsan Kaynakları Yönetimi; İş Stresi; Stres Yönetimi